POLITIK HUKUM DAN UPAYA POSITIVISASI HUKUM ISLAM DI INDONESIA: STUDI TENTANG KONFLIK HUKUM DALAM UNDANG-UNDANG PERKAWINAN DAN UNDANG-UNDANG PERADILAN AGAMA - Bani Syarif Maula (IAIN Purwokerto, 2015)
Abstract: The politics of law that ignore the aspirations of society has led to inconsistency in the application of the law because of the differences between the will of the people with the legislation. This study specifically examines the political law in terms of the application of Islamic law in Indonesia which is envisaged in Law No. 1/1974 on Marmage and the Law 7/1989 on Religious Courts (and its amendment Law No. 3/2006). The political situation that characterizes the formation of the Marriage Law and the Law on Religious Courts clearly show trends and policy direction of the state law. It can be seen from the political aspects of the legal establishment, the political aspects of the content of the law (principles and the rule of law), and political aspects of law enforcement. These three aspects have made Islamic law practiced by the Indonesian Muslim community (the living laws) in conflict with formal legal rules defined by the state. The conclusion from this study is that the legal provisions in the Mariage Law that conflict, namely: Article 2 paragraph (1), Article 7 (1), Article 31 paragraph (3) and Article 34 paragraph (1) and (2), as well as Article 42 and 43 paragraph (1). While the legal provisions in the Law on Religious Courts where a conflict is Article 50 of Law No. 7/1989 and Article 50 paragraph (1) and (2) of Law No. 3/2006 (amendment of the same article of the Law No. 7/1989) Keywords: Politics, Law, Conflict of Laws, Islamic Law, Marriage Law, the Law on Religious Courts